Five-year clinical efficacy and safety of contemporary thin-strut biodegradable polymer versus durable polymer drug-eluting stents: a systematic review and meta-analysis of 9 randomized controlled trials - Tomoaki Kobayashi (2019)
© 2019, Japanese Association of Cardiovascular Intervention and Therapeutics. Very long-term data of the biodegradable polymer drug-eluting stents (BP-DES) in comparison with the contemporary durable polymer DES (DP-DES) are still to be investigated. We aimed to investigate the very long-term clinical performance of contemporary BP-DES against the DP-DES. We performed a systematic review to evaluate very long-term clinical outcomes of BP-DES versus DP-DES. Inclusion criteria were randomized design comparing BP-DES against DP-DES and follow-up duration ≥ 36 months. MEDLINE, EMBASE, and CENTRAL without restricting language or publication status were searched up to December 2018. The primary efficacy and safety endpoints were target lesion failure (TLF; a composite of cardiac death, target vessel myocardial infarction and ischemia-driven target lesion revascularization) and definite/probable stent thrombosis (ST), respectively. Primary analysis was done for the contemporary thin-strut BP- and DP-DES (strut thickness < 100 µm). A total of 9 trials comprising 10,699 patients (BP-DES, n = 6241 versus DP-DES, n = 4458) were analyzed. The mean follow-up duration was 63 months. No significant difference was found in TLF [Odds ratio (95% CI) 1.04 (0.89–1.21)] and definite/probable ST (odds ratio (95% CI) 0.78 (0.59–1.01)] between the BP- and DP-DESs. The present meta-analysis suggested that the contemporary thin-strut BP- and DP-DES have similar efficacy and safety profile at 5-year follow-up. Clinical trial registration PROSPERO; CRD42018101983 https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=101983.